Why It Is Not Always Anxiety: A Tough Diagnosis of Stiff Person Syndrome - Carmen Elena Cervantes; Hsien Lee Lau; Tina Ataian Binazir; Keith O. O’Brien; Jonathan S. Cross (Case Reports in Neurological Medicine)
Anxiety disorder is a commonly used diagnosis that may mask underlying conditions. Stiff person syndrome (SPS) is a rare neuroimmunological disorder characterized by progressive rigidity and painful muscle spasms affecting axial and lower extremity musculature. These episodes can be triggered by sudden movement, noise, or emotional stress, which may present as a psychiatric condition. We report the case of a 30-year-old female who presented with recurrent panic attacks with multiple prior hospital admissions for anxiety, rigidity, and difficulty in walking. Previous electroencephalogram (EEG) and brain and cervical spine magnetic resonance imaging (MRI) were unremarkable. She was empirically treated with diazepam and beta-blockers for SPS, which was confirmed by positive glutamic acid decarboxylase (GAD) antibodies. The patient’s symptoms became refractory to benzodiazepines and required steroids with intravenous immunoglobulin (IVIG). Her rigidity subsequently responded to plasmapheresis. In SPS, antibodies in the cerebrospinal fluid (CSF) most commonly target the GAD antigen on gamma-aminobutyric acid (GABA) neurons. The goal of treatment is to ameliorate symptoms and improve quality of life. Our case of SPS was masked as generalized anxiety disorder for at least six years since onset of symptoms. The criteria for both diagnoses may overlap as seen in this patient.